Design of a Full-Directional and Light-Weight Electric Vibrator - Baochao Wang; Chenyuan Lu; Qingtao Zong; Dongwei Wang; Alim Pulatov; Shuqi Shang (IEEE Access)
Vibrators are widely used in agriculture, such as for vibrating trees to harvest fruits and nuts, or for vibrating screens to separate different materials (e.g. plants and soil or grain and debris) in the harvesting process. Traditional vibrators are bulky and configured with fixed mechanical transmission, so they cannot be precisely controlled and cannot adapt to different conditions, causing negative effects such as ineffective vibration or damaging tree barks. In this paper, a full-directional and lightweight electric vibrator is designed. The unidirectional vibration force is produced through the utilization of two centrifugal forces that are generated by the eccentric mass rotation of two motors. Firstly, the vibration direction can be adjusted to any direction by adjusting the meeting position of the two centrifugal forces. Secondly, the vibration force can be adjusted by changing the motor speed, as the centrifugal force is proportional to the square of the rotation speed. The vibrator is tested with laboratory bench experiment and with agricultural application for vibrating a tree. The prototype vibrator can produce 680N with the weight of 7.2kg, the force can be further improved by increasing the eccentric mass, increasing the rotation speed or decreasing the rotation arm length. The vibrator can be applied to smart agriculture, such as nut and fruit harvesting, or adaptive vibration screening.